Digital Health for Patients With Multiple Myeloma: An Unmet Need. (2021) - Jagannath, Sundar; Mikhael, Joseph; Nadeem, Omar; Raje, Noopur
Abstract : Multiple myeloma (MM) is associated with the highest symptom burden and lowest health-related quality of life (HRQoL) among patients with hematologic malignancies. HRQoL in MM is heterogeneous, varying over the course of disease, with the highest burden at diagnosis and relapse. Patients with MM are increasingly being treated with oral maintenance medications at home. As a result, longitudinal monitoring of medication adherence and patient-reported outcomes, including HRQoL, could inform on disease status, therapeutic tolerability, and satisfaction with care. Digital health technologies, including telemedicine, mobile health, and wearable devices, are poised to become an integral part of modern health care, in part due to the surge in telemedicine necessitated by the COVID-19 pandemic. Although the literature has many reports on the use of digital health technologies in other types of cancers, fewer studies report on their application to MM. In the current narrative review, we survey the applications of digital health for MM. Although there is evidence that some are associated with improved health outcomes, challenges exist that must be met to ensure more widespread adoption. These include the need for increased awareness by patients and health care providers, lack of access by the typical older patient with MM, absence of randomized clinical trials, and low integration with current workflows such as electronic health records. Following our summary of technologies that could benefit patients with MM, we end by describing our vision for how they can be integrated into each phase of the patient journey.